CDN Głos Wolnego Robotnika . no. 95, 1984 - Międzyzakładowy Robotniczy Komitet "Solidarności" ([s.n.], 1984)
Creation and circulation: For issues no. 1-80 edition A assumed to be the primary edition.Published in variations: editions B,C,D,E,F. From issue no. 81 published without variations and omiting the edition statement